Inhibition of Cyclin-Dependent Kinase 9 Downregulates Cytokine Production Without Detrimentally Affecting Human Monocyte-Derived Macrophage Viability - McHugh, Brian J.; Stephen, Jillian; Robb, Calum T.; Fox, Sarah; Kipari, Tiina; Cartwright, Jennifer A.; Haslett, Christopher; Duffin, Rodger; Lucas, Christopher D.; Rossi, Adriano G. (Frontiers in Cell and Developmental Biology, 2022)
Cyclin-dependent kinase (CDK) inhibitor drugs (CDKi), such as R-Roscovitine and AT7519, induce neutrophil apoptosis in vitro and enhance the resolution of inflammation in a number of in vivo models. This class of compounds are potential novel therapeutic agents that could promote the resolution of acute and chronic inflammatory conditions where neutrophil activation contributes to tissue damage and aberrant tissue repair. In this study we investigated CDKi effects on macrophage pro-inflammatory mediator production and viability. Treatment of human monocyte-derived macrophages (MDMs) with the CDKi AT7519 and R-roscovitine at concentrations that induce neutrophil apoptosis had no significant effect on control or LPS-activated MDM apoptosis and viability, and did not detrimentally affect MDM efferocytosis of apoptotic cells. In addition, enhanced efferocytosis, induced by the glucocorticoid dexamethasone, was also unaffected after a short time treatment with R-Roscovitine. Macrophage cytokine responses to inflammatory stimuli are also of importance during inflammation and resolution. As a key target of CDKi is CDK9, involved in protein transcription via the RNA polymerase II complex, we investigated the effect of CDKi drugs on cytokine production. Our data show that treatment with AT7519 significantly downregulated expression and release of key MDM cytokines IL-6, TNF, IL-10 and IL-1beta, as well as markers of pro-inflammatory macrophage polarization. R-Roscovitine was also able to downregulate inflammatory cytokine protein secretion from MDMs. Using siRNA transfection, we demonstrate that genetic knock-down of CDK9 replicates these findings, reducing expression and release of pro-inflammatory cytokines. Furthermore, overexpression of CDK9 in THP-1 cells can promote a pro-inflammatory phenotype in these cells, suggesting that CDK9 plays an important role in the inflammatory phenotype of macrophages. Overall, this study demonstrates that pharmacological and genetic targeting of CDK9 inhibits an inflammatory phenotype in human MDMs. As such these data indicate that CDK9 may be key to therapeutically targeting pro-inflammatory macrophage functions during chronic inflammation.